Lactobacillus plantarum Strains Can Enhance Human Mucosal and Systemic Immunity and Prevent Non-steroidal Anti-inflammatory Drug Induced Reduction in T Regulatory Cells - de Vos, Paul; Mujagic, Zlatan; de Haan, Bart J.; Siezen, Roland J.; Bron, Peter A.; Meijerink, Marjolein; Wells, Jerry M.; Masclee, Ad A. M.; Boekschoten, Mark V.; Faas, Marijke M.; Troost, Freddy J. (Frontiers in Immunology, 2017)
Orally ingested bacteria interact with intestinal mucosa and may impact immunity. However, insights in mechanisms involved are limited. In this randomized placebo-controlled cross-over trial, healthy human subjects were given Lactobacillus plantarum supplementation (strain TIFN101, CIP104448 or WCFS1) or placebo for 7 days. To determine whether L. plantarum can enhance immune response, we compared the effects of three stains on systemic and gut mucosal immunity, by among others assessing memory responses against tetanus toxoid-antigen, and mucosal gene transcription, in human volunteers during induction of mild immune stressor in the intestine, by giving a commonly used enteropathic drug, indomethacin (NSAID). Systemic effects of the interventions were studies in peripheral blood samples. NSAID was found to induce a reduction in serum CD4+/Foxp3 regulatory cells, which was prevented by L. plantarum TIFN101. T-cell polarization experiments showed L. plantarum TIFN101 to enhance responses against tetanus toxoid-antigen, which indicates stimulation of memory responses by this strain. Cell extracts of the specific L. plantarum strains provoked responses after WCFS1 and TIFN101 consumption, indicating stimulation of immune responses against the specific bacteria. Mucosal immunomodulatory effects were studied in duodenal biopsies. In small intestinal mucosa, TIFN101 upregulated genes associated with maintenance of T and B-cell function and antigen-presentation. Furthermore, L. plantarum TIFN101 and WCFS1 downregulated immunological pathways involved in antigen-presentation and shared downregulation of snoRNAs, which may suggest cellular destabilization, but may also be an indicator of tissue repair. Full sequencing of the L. plantarum strains revealed possible gene clusters that might be responsible for the differential biological effects of the bacteria on host immunity. In conclusion, the impact of oral consumption L. plantarum on host immunity is strain dependent and involves responses against bacterial cell components. Some strains may enhance specific responses against pathogens by enhancing antigen presentation and leucocyte maintenance in mucosa. In future studies and clinical settings, caution should be taken in selecting beneficial bacteria as closely related strains can have different effects. Specific bacterial strains can prevent immune stress induced by commonly consumed painkillers such as NSAID and can have enhancing beneficial effects on immunity of consumers by stimulating antigen presentation and memory responses.